The link between the self and the fear of missing out in marketing - Çeliktutan, Begüm. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
With the advancements in technology, today’s consumers have a vast amount of alternatives available for every consumption decision in their lives. The availability of alternatives enriches the lives of consumers, yet it is also tiring to be exposed to endless number of opportunities, since pursuit of them all is not possible. In these conditions, consumers are left out with the all-consuming feeling that others might be having more rewarding experiences than them, or as commonly referred, they experience Fear of Missing Out (FOMO). Although it is popular in press and used widely in marketing communication strategies, research on FOMO in the context of marketing is very limited. To provide insights on the profile of people who are more prone to experience higher levels of FOMO, present research mainly investigates FOMO’s link to self. A survey study (N = 412) was conducted to explore FOMO’s relation to individual differences in social comparison orientation, trait anxiety, attachment, need to belong, self-esteem, extroversion and neuroticism; and behavioral consequences of brand loyalty and word of acceptance tendency. Results of the regression analysis demonstrated that FOMO is associated with need to belong, social comparison orientation, trait anxiety, and attachment anxiety; whereas extraversion moderates the relationship between social comparison orientation and FOMO. Mediating role of anxiety in the relationship between self-esteem, neuroticism and FOMO is also tested. FOMO is also found to be correlated to WOM acceptance tendency and cognitive loyalty. Practical implications and suggestions for future research are discussed.
Keywords: Marketing research.; Brand loyalty -- Analysis.; Consumption (Economics)